Buenas prácticas inclusivas en recreos y deporte en edad escolar (EDITUM. Ediciones de la Universidad de Murcia, 2025)
Society and its institutions are in the process of recognizing game and inclusive sport as main sources of physical activity and their relationship with emotional and social physical health. The school is a fundamental engine in this process, since it shows a greater number of good playful and sports inclusive practices, which can be replicated in other formal and non -formal areas in which schoolchildren develop. This publication gives an account of all this and the contents collected in the same bring knowledge and experiences of good practices presented by numerous experts and professionals from different fields (national and international) in the field of inclusion, play and sport. This book marks undoubtedly a fundamental milestone in the subject that addresses and surely is very useful for those families, professionals and educational administrations that want to strengthen a school for all, an inclusive school where leisure, play and inclusive sport are among its basic references.